Acceptance and commitment therapy for individuals at risk for psychosis or with a first psychotic episode: a qualitative study on patients' perspectives - Bouws, Jara; Henrard, Ann; de Koning, Mariken; Schirmbeck, Frederike; van Ghesel Grothe, Sophia; van Aubel, Evelyne; Reininghaus, Ulrich; de Haan, Lieuwe; Myin-Germeys, Inez (Early intervention in psychiatry, 2024)
Aim The aim of this qualitative study is to explore patients' perspectives on Acceptance and Commitment Therapy for early stages of psychosis. Therefore, we interviewed participants of the INTERACT study, that quantitatively investigated Acceptance and Commitment Therapy in Daily Life (ACT-DL) in combination with treatment as usual, for early stages of psychosis, comparing it to treatment as usual. Methods Within 6 months after finishing ACT-DL, we conducted semi-structured, individual interviews with 19 participants. All interviews were audio-recorded and transcribed. Thematic analysis was used for coding and analysis. Results Two overarching themes were formed: ‘the meaning of ACT’ and ‘what to improve’. Considering the first, participants generally understood and connected with the meaning of ACT, noticing more awareness and acceptance of their thoughts and feelings, and living more in line with their personal values. The second theme included comments on the protocol not being personal or psychosis specific enough and some elements of ACT being too difficult to understand when having active psychotic symptoms. Conclusions This study suggests that ACT is an acceptable and promising new form of treatment for early stages of psychosis, and it provides relevant information to further develop ACT for this group.